Clinical effects of buprenorphine on open field behaviour and gait symmetry in healthy and lame weaned piglets. Issue 3 (December 2015) - Meijer, Ellen; van Nes, Arie; Back, Willem; van der Staay, Franz Josef
Highlights: Two methods to quantify pain associated with lameness are assessed using the strong analgesic buprenorphine. Gait asymmetry in lame pigs, measured by kinetic pressure mat analysis, decreased after administering buprenorphine. Activity in an open field test increased after buprenorphine administration. Abstract: Lameness in pigs decreases animal welfare and economic profit for the farmer. An important reason for impaired welfare in lame animals is pain due to lameness. No direct measurement of pain is possible in animals, and methods to indirectly detect and quantify the amount of pain an animal is experiencing are urgently needed. In this study, two methods to assess pain associated with lameness in pigs were evaluated to determine if they were sensitive enough to detect a lameness reduction as an effect of an experimental analgesic medication. Asymmetry associated with lameness was objectively quantified using pressure mat kinetic parameters: peak vertical force (PVF), load rate (LR), vertical impulse (VI) and peak vertical pressure (PVP). Locomotor activity was assessed in an open field test. A dose of 0.04 mg/kg buprenorphine, a strong analgesic, was used to treat 10 lame pigs, while eight other lame pigs, treated with physiological saline solution, served as controls. Buprenorphine decreased lameness-associated asymmetry for pressure mat LR ( P  = 0.002), VI ( P  = 0.003) and PVP ( P  = 0.001) and increased activity of the lame pigs in the open field ( P  = 0.023), while saline-treated animals did not show any changes in asymmetry and became less active in the open field ( P  <   0.001). It was concluded that measurement of gait asymmetry by pressure mat analysis and locomotor activity in an open field test are both sensitive enough to detect the analgesic effects of buprenorphine when used to treat moderate to severe clinical pain in a relatively small group of affected pigs. The methods used in this study may also provide promising additional tools for future research into early pain recognition and lameness treatment in pigs.